Post-Therapy Sense of Taste Disorders in Nasopharyngeal Carcinoma - Baiq Auliya Cahya Putri (Rifa'Institute, 2021)
Nasopharyngeal Carcinoma (NPC) or Nasopharyngeal Carcinoma (NPC). Many are found in Indonesia. Radiotherapy as the gold standard for nasopharyngeal carcinoma (NPC). This study aims to determine the relationship between radiation therapy in NCP and taste disorders. article review. Conventionally for early stage NPC radiation (T1, T2) given at a dose of 200 - 220 cGy per fraction, given 5 times a week without rest. up to a total dose of 6000 - 7000 cGy in 6 weeks. As for NPC with a larger tumor size (T3 and T4), a higher total radiation dose was given to the primary tumor in the nasopharynx, namely 7000-7500 cGy.: There is a relationship between nasopharyngeal carcinoma therapy with the ability to feel.